(untitled) (Padmakanya Journal of Science and Technology, 2025)
Municipal tap and Jar water are the common drinking water sources for the residents of Kathmandu. This study was conducted to analyze the water quality of jar and tap water of Kathmandu valley between November 2023 and April 2024. Altogether 30 water samples; 15 tap water and 15 jar water were assessed during this study. Based on analysis, physicochemical parameters such as temperature, conductivity, TDS, chloride, alkalinity, hardness was found to be within drinking water quality guidelines of NDWQS, 2022. However, pH was out of recommended range. The bacteriological analysis revealed that only 5 tap waters were within the recommended limit whereas entire jar water exceeded recommended range. Four different enteric bacteria namely, E. coli (24%), Klebsiella spp. (29%), Pseudomonas spp. (33%), Enterobacter spp. (14%) was isolated from tap water samples. Likewise, five different enteric bacteria such as E. coli (38 %), Klebsiella spp. (22%), Pseudomonas spp. (16%), Enterobacter spp. (19%) and Citrobacter spp. (5%) were isolated from jar water samples. Antibiotic susceptibility test revealed that most of E. coli, Pseudomonas spp., Enterobacter spp. isolates were found to be sensitive against Chloramphenicol, Norfloxacin, Gentamicin but resistant against Ampicillin. Most of Klebsiella spp. isolates were sensitive against, Azithromycin, but resistant against Ampicillin and cefoxitin. Similarly, isolated Citrobacter spp. were resistant to Ampicillin, Cefoxitin whereas sensitive against Norfloxacin. 23.8% of tap water isolates and 18.9% of jar water isolates were Multiple Drug Resistant. In conclusion, majority of the samples of drinking water were not safe for direct consumption and were found to be microbially unsafe and presence of multiple drug-resistant bacteria which may cause serious health hazards. Hence, regular monitoring of water quality, proper distribution system and treatment is necessary.